Pluralism of Papuan Student Community Acceptance in Makassar City - Dian Riani Said; Andi Trisnowali MS; Jihan Fahriana Salahuddin; Rosliana Cerlianti (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Indonesia is a plural country, in terms of culture, ethnicity, language, and religion. This shows that a diverse Indonesia has the potential to cause disputes between ethnicities. One of them is the existence of a Papuan student community outside the region often get less pleasant treatment. The condition of Makassar city is one of the compound areas or has diversity. Almost all the different tribes in Indonesia inhabit the city of Makassar. The possibility of conflict can occur from its demographics, even being criminalized to the Papuan student community that inhabits the city of Makassar can occur. There is a difference that occurs in the city of Makassar, the Papuan student community tends to be acceptable in comparison to other areas, can be seen from the many Papuan community dormitories located in the city of Makassar. The results explained that the good relations of the people of Makassar city with the Papuan student community can not be separated from the fact of a long history, that Makassar is the Pusar area of Eastern Indonesia, and Papua was once part of the spread of Makassar Bugis traders. However, maintaining good relations with the surrounding residents is the most important thing to create a harmonious situation, uphold the value of tolerance and open up to new environments. As well as avoiding mis-information that reaches the community of Makassar city about Papua that smells negative, to prevent the widespread spread of OPM understanding in the city of Makassar.